Target Markets, Socialization Channels of Diverse Cultural Expressions in Sustainable Urban Communities - Zambrano, Lilia Moncerratte Villacís; Marcillo, Víctor Aurelio Mero; Macias, José Darwin Zambrano; Zamora, Yadira Maribel Sánchez; Vera, Vilma Estela Alcivar; Falcones, Ana Cecilia Vélez (Journal of Ecohumanism, 2025)
Objective: This research aimed to analyze the diverse cultural manifestations embedded within communities, particularly as expressed through artistic expressions among the university population of the Sucre Extension. Method: A quantitative and qualitative approach was employed. Data was collected through surveys and analyzed using SPSS 27. The reliability of the instrument was verified using Cronbach's alpha, yielding a coefficient of 0.96. Results and Discussion: The findings confirmed that ancestral ludic expressions serve as a primary channel for defining Montubio identity. If nurtured, these expressions could become a target market that fulfills the need to preserve the historical presence of the culture. This perspective promotes local traditions, including dances, oral traditions, and ancestral gastronomy. The study concludes that culture plays a significant role in target markets, not only for promoting cultural heritage but also for maintaining the ancestral identity of the Z generation.